Structural Idealism : a Theory of Social and Historical Explanation. - Mann, Douglas (Wilfrid Laurier University Press, 2006)
Do we determine our actions, or are our actions ruled by the structure of our society? Does our culture create us, or do we create our culture? Within history and social theory there is a fundamental division of opinion between those who explain human action by considering the intentions, reasons and motives of individuals and those who use broader social structures. Structural Idealism presents a theory of social and historical explanation which argues that "idealists" such as Hegel, who champion human agency, and "materialists" such as Marx, who support social structure, have grasped but.